Measurement of the CP-violating phase sJ/ψ using the flavor-tagged decay Bs0→J/ψ in 8fb -1 of pp̄ collisions - Abazov, V. M.; Abbott, B.; Acharya, B. S.; Adams, M.; Adams, T.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; Alves, G. A.; Aoki, M.; Arov, M.; et al. (American Physical Society (APS), 2012)
We report an updated measurement of the CP-violating phase, sJ/ψ, and the decay-width difference for the two mass eigenstates, ΔΓ s, from the flavor-tagged decay Bs0→J/ψ. The data sample corresponds to an integrated luminosity of 8.0fb -1 accumulated with the D0 detector using pp̄ collisions at √s=1.96TeV produced at the Fermilab Tevatron collider. The 68% Bayesian credibility intervals, including systematic uncertainties, are ΔΓ s=0.163-0.064+0. 065ps -1 and sJ/ψ=-0.55-0.36+0.38. The p-value for the Standard Model point is 29.8%. © 2012 American Physical Society.